Analysis Of The Impact Of The Existence Of Kabinuang Waste Landfill On The Socio-Economic Conditions Of Local Scavengers (Case Study Of Kabinuang Waste Landfill, Tolitoli Regency) - Febrina, Febrina; Dg Marumu, Moh. Natsir (STIE Mujahidin Tolitoli Development Economics Study Program, 2024)
This study aims to determine the impact of the existence of the Kabinuang Waste Final Disposal Site (TPA) on the socio-economic conditions of local scavengers around it. This study uses a qualitative research method with a descriptive approach. The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawn. Based on the research and the results of the discussion, it can be concluded that there is an influence on the scavenger community around the Kabinuang Landfill. many scavengers derive their main income from scavenging work, with varying amounts, which are directly related to activities at the Kabinuang Landfill. However, in addition to that, it also affects the inadequate living conditions of scavengers because the physical building is vulnerable to danger. In addition, education levels among scavengers are still low, with many scavenger children dropping out of school due to cost constraints.